Analysis Of The Communication Network Structure Of The Keyword “Rempang” On Twitter Using A Social Network Analysis Approach - Lukman, Rismawati; Andi Alimuddin Unde; Hasbi Marissangan; Ahmad Musafir; Elvis Tinting Paembonan; Elsa Claudia Salman; Nur Kalbina Razak (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2024)
On September 7, 2023, a clash occurred on Rempang Island, Batam City, Riau Islands, between residents and joint officers, resulting in injuries to students and community members. The Rempang conflict was widely discussed on social media, particularly on Twitter, where 1010 tweets were made using the hashtag #Rempang. This research aims to identify the key actors behind the emergence of the hashtag #Rempang and analyze the type of relationships and the communication network structure that developed. The research method employed is the Social Network Analysis (SNA) approach, which focuses on studying relationships and is used to measure these relationships and extract information from individuals using the Gephi application. The study results indicate that the communication network exhibits a two-mode relationship type, with three distinct network patterns: wheel, Y, and chain communication patterns. The relationships within the network are direct and directional. The research also reveals a main actor, @tempodotco, who has a degree centrality and in-degree value of 404. The relationships between actors in this communication network are very close, highlighting the significance of @tempodotco in the dissemination and discussion of the Rempang conflict on social media.